2013
DOI: 10.1371/journal.pone.0053324
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cell Detachment on the Respiration Rate of Tumor and Endothelial Cells

Abstract: Cell detachment is a procedure routinely performed in cell culture and a necessary step in many biochemical assays including the determination of oxygen consumption rates (OCR) in vitro. In vivo, cell detachment has been shown to exert profound metabolic influences notably in cancer but also in other pathologies, such as retinal detachment for example. In the present study, we developed and validated a new technique combining electron paramagnetic resonance (EPR) oximetry and the use of cytodex 1 and collagen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…In ad di tion to apop to sis, var i ous other bi o log i cal processes can lead to cell de struc tion. Anoikis is re lated to apop to sis as it is a cas pase de pen dent cell death mech a nism trig gered by the de tach ment of cells from the ex tra cel lu lar ma trix [9,110,111]. Necro sis, as op posed to the highly reg u lated apop to sis, is an ac ci den tal death oc cur ring spon ta neously fol low ing ex ter nal stresses that block nor mal phys i o log i cal processes.…”
Section: Metabolic Regulation Of Cancer Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…In ad di tion to apop to sis, var i ous other bi o log i cal processes can lead to cell de struc tion. Anoikis is re lated to apop to sis as it is a cas pase de pen dent cell death mech a nism trig gered by the de tach ment of cells from the ex tra cel lu lar ma trix [9,110,111]. Necro sis, as op posed to the highly reg u lated apop to sis, is an ac ci den tal death oc cur ring spon ta neously fol low ing ex ter nal stresses that block nor mal phys i o log i cal processes.…”
Section: Metabolic Regulation Of Cancer Cell Deathmentioning
confidence: 99%
“…In ter est ingly, cell de tach ment from the ex tra cel lu lar ma trix and neigh bor ing cells is per se able to in duce early meta bolic changes, in clud ing di ver sion of glu cose from gly col y sis and the TCA cy cle to the PPP [9], and de creases the oxy gen con sump tion rate [111]. The PPP is an an a bolic path way that pro duces NADPH, a co fac tor nec es sary for glu tathione re cy cling and ROS detox i fi ca tion.…”
Section: Metabolic Contribution To Cancer Metastasismentioning
confidence: 99%
“…10,11 In vitro studies of melanoma and endothelial cell lines have demonstrated cell detachment to result in decreased respiration and glucose consumption, implying metabolic reprogramming toward a less oxidative phenotype. 12,13 Despite a lower glucose uptake, these detached cells maintain lactate production, indicating use of alternative nutrients, for example, glutamine as energy substrates. 13 Altogether, these findings support the idea of malignant cell metabolic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Despite a lower glucose uptake, these detached cells maintain lactate production, indicating use of alternative nutrients, for example, glutamine as energy substrates. 13 Altogether, these findings support the idea of malignant cell metabolic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have shown that the amount of superoxide generated from leukocytes in suspension is proportional to a cell density, whereas it is inversely related to the cell density in adherent cells due to the mutual contact-induced suppression of the radical generation [22]. Another study proved that detached cells consume significantly less oxygen than adherent cells in both murine melanoma and human umbilical vein endothelial cells, indicating a considerable effect of the adhesion/ detachment process on the cell respiration rate [23]. It is therefore necessary to develop an EPR microscopy that enables us to accurately examine the redox state of a cell in the adhesion state, i.e., in situ, in combination with a conventional optical microscope.…”
Section: Introductionmentioning
confidence: 99%